2014
DOI: 10.1162/pres_a_00194
|View full text |Cite
|
Sign up to set email alerts
|

Achieving Participant Acceptance of their Avatars

Abstract: An experiment was carried out to examine the extent to which an avatar can be perceived by people as similar to themselves, including their face and body. The avatar was judged by the participants themselves rather than by third parties. The experiment was organized in two phases. The initial phase consisted of a forced-choice, paired comparison method used to create a ranking of 10 virtual faces in order of preference. This set of faces included a facial mesh, created by a custom software pipeline to rapidly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…In all cases participants were requested to maintain a neutral facial expression to avoid emotion processing during the observation, since it has been shown that emotions on faces generate different brain traces and activate mirror neurons (Likowski et al, 2012 ). Avatars were generated in a matter of minutes using the fast creation of look-alike avatars pipeline described in Blom et al ( 2014 ). The resultant avatars were tweaked manually to make minor smoothing and lighting improvements.…”
Section: Methodsmentioning
confidence: 99%
“…In all cases participants were requested to maintain a neutral facial expression to avoid emotion processing during the observation, since it has been shown that emotions on faces generate different brain traces and activate mirror neurons (Likowski et al, 2012 ). Avatars were generated in a matter of minutes using the fast creation of look-alike avatars pipeline described in Blom et al ( 2014 ). The resultant avatars were tweaked manually to make minor smoothing and lighting improvements.…”
Section: Methodsmentioning
confidence: 99%
“…In addition they all suffer from privacy issues, as in order to obtain a metrically accurate avatar the subject needs to be scanned in minimal clothing condition. Blom et al [15] present a pipeline for generating look-alike avatars using a combination of artistic, depth, and image-based approaches; they perceptually evaluate their avatars to be 7.5 out of 10 on a likeness rating. A difficulty with photo-realistic body scans can sometimes be the Uncanny Valley, or the sensation that the avatar is strange because it approaches life-like visual quality but does not reach it [48].…”
Section: Technological Approachesmentioning
confidence: 99%
“…For instance, Shapiro et al (2014) and Waltemate et al (2018) used 3D cameras and photogrammetry, respectively, to capture 3D models of their users. Singular Inversions FaceGen Modeller 14 has also been employed to generate 3D faces from user photos and then apply them to a general 3D avatar body (Blom et al, 2014;Gonzalez-Franco et al, 2016). However, scanning approaches require the ability to physically scan the user, limiting their use for certain applications, particularly remote ones.…”
Section: Virtual Avatar Resourcesmentioning
confidence: 99%